Whole Transcriptome Screening Reveals Myelination Deficits in Dysplastic Human Temporal Neocortex. (21st January 2016) - Donkels, Catharina; Pfeifer, Dietmar; Janz, Philipp; Huber, Susanne; Nakagawa, Julia; Prinz, Marco; Schulze-Bonhage, Andreas; Weyerbrock, Astrid; Zentner, Josef; Haas, Carola A.
Abstract: Focal cortical dysplasias (FCDs) are local malformations of the human neocortex with strong epileptogenic potential. To investigate the underlying pathomechanisms, we performed a whole human transcriptome screening to compare the gene expression pattern of dysplastic versus nondysplastic temporal neocortex. Tissue obtained from FCD IIIa cases (mean age 20.5 years) who had undergone surgical treatment, due to intractable epilepsy, was compared with nondysplastic specimens (mean age 19.9 years) by means of Affymetrix arrays covering 28 869 genes. We found 211 differentially expressed genes (DEX) among which mainly genes important for oligodendrocyte differentiation and myelination were downregulated in FCD IIIa. These findings were confirmed as functionally important by Database for Annotation, Visualization, and Integrated Discovery (DAVID) analysis. The reduced expression of myelin-associated transcripts was confirmed for FCD Ia, IIa, and IIIa by real-time RT–qPCR. In addition, we found that the density of myelin basic protein mRNA-expressing oligodendrocytes and of 2′, 3′-cyclic nucleotide 3′-phosphodiesterase-positive myelin fibers was significantly reduced in dysplastic cortex. Moreover, high-resolution confocal imaging and 3D reconstruction revealed that the myelin fiber network was severely disorganized in dysplastic neocortex, indicating a disturbance of myelin sheath formation and maintenance in FCD.